2017
DOI: 10.1097/mlr.0000000000000728
|View full text |Cite
|
Sign up to set email alerts
|

The Monthly Cycle of Hypoglycemia

Abstract: Background Multi-payer initiatives have sought to address social determinants of health, such as food insecurity, by linking primary care patients to social services. It remains unclear whether such social determinants contribute to avoidable short-term healthcare costs. Objectives We sought to quantify costs and mitigating factors for the increased risk of hypoglycemia at the end of each month among low-income Americans, a phenomenon related to exhaustion of food budgets. Research design We used claims da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 29 publications
(27 reference statements)
2
29
0
Order By: Relevance
“…Another study [17] concluded the association of poor glycemic control and severe hypoglycemia in contradiction to the present findings. Previous researches [22, 27] observed higher severe hypoglycemia among patients with foods insecurity especially among patients with household income below the national income, furthermore, the highest rate of hospital admission with hypoglycemia was commoner during the last week of the month due to exhaustion of food budget. In the current study, no relation between food insufficiency and hypoglycemia risk, a plausible explanation may be the difference in income and other socio-demographic characteristics or the small size of the present sample.…”
Section: Discussionmentioning
confidence: 97%
“…Another study [17] concluded the association of poor glycemic control and severe hypoglycemia in contradiction to the present findings. Previous researches [22, 27] observed higher severe hypoglycemia among patients with foods insecurity especially among patients with household income below the national income, furthermore, the highest rate of hospital admission with hypoglycemia was commoner during the last week of the month due to exhaustion of food budget. In the current study, no relation between food insufficiency and hypoglycemia risk, a plausible explanation may be the difference in income and other socio-demographic characteristics or the small size of the present sample.…”
Section: Discussionmentioning
confidence: 97%
“…A study evaluating hospital admissions found a 27% increase in admissions for hypoglycaemia for low-income diabetics in the last calendar week of the month compared to the first week (Seligman et al, 2014). A more recent study, found increased odds of ED visit or hospital admission for hypoglycaemia in patients with household incomes less than the national median during Week 4 compared to earlier weeks (Basu, Berkowitz, & Seligman, 2017). Overall, studies show that low-income households struggle with paying for basic needs towards the end of the month, including food, which would be a heavily competing priority for households who purchase cell phone minutes only when they can afford them.…”
Section: Discussionmentioning
confidence: 99%
“…One study illustrating the former concept demonstrated that low-income individuals were more likely to report to the ED for hypoglycemia at the end of the month, as opposed to the beginning of the month. 23 …”
Section: Limitationsmentioning
confidence: 99%